Rhabdomyolysis induced by excessive coffee drinking. (August 2014) - Chiang, W-F; Liao, M-T; Cheng, C-J; Lin, S-H
Excessive ingestion of caffeine-containing beverages is a rare cause of rhabdomyolysis. Here, we describe the case of a 44-year-old woman presented with nausea, vomiting, palpitations, and tea-colored urine 6 h after drinking a liter of black coffee containing approximately 565 mg of caffeine for mental alertness. Laboratory studies were notable for myoglobinuria and markedly elevated plasma creatine kinase (CK) level of 7315 U/L. With volume expansion and alkalization, her plasma CK level returned to normal within 5 days. Rhabdomyolysis should be considered a potential health hazard from excessive consumption of caffeine-containing products.